IPTEKS PROSEDUR PENARIKAN ASET TETAP BERWUJUD PADA PT. PLN (PERSERO) UP3 MANADO - Simanjuntak, Lucyana Aprillya; Mamontoh, Dewi Larasati; Afandi, Dhullo (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. PLN (Persero) Manado UP3 is one of the State-Owned Enterprises that is engaged in services, the purpose of which is to try to provide electricity in sufficient quantities and quality to regulate the burden of various places. This electricity supply is sought to provide services to the community, namely as a production infrastructure and as a fulfillment of people's daily needs. The problems studied in this study are: 1) What is the procedure for withdrawal of Fixed Assets at PT. PLN (Persero) Manado UP3, the observation of this study are: 1) To find out how the procedure of delivering tangible fixed assets at PT. PLN (Persero) Manado UP3. The object of this research is PT. PLN (Persero) Manado UP3. Data retrieval is done by means of documentation and interviews at PT. PLN (Persero) Manado UP3. The results of the observation show that in practice the Procedure for Withdrawing Fixed assets at PT. The PLN (Persero) Manado UP3 is not good because of the long period of determination and responsiveness of the officers, which takes a long time. It would be better if in the procedure of managing fixed assets at PT. PLN (Persero) Manado UP3 is more responsive and the decline in its determination is accelerated.Keywords: procedure, fixed assets